2017
DOI: 10.7150/ijms.20504
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Yes-Associated Protein Induces the Apoptosis While Inhibits the Proliferation of Human Periodontal Ligament Stem Cells through Crosstalk between Erk and Bcl-2 Signaling Pathways

Abstract: Objective: The purpose of this study was to provide an insight into the biological effects of knockdown Yes-associated protein (YAP) on the proliferation and apoptosis of human periodontal ligament stem cells (h-PDLSCs). Methods: Immunofluorescence and Western blot were used to evaluate Hippo-YAP signaling expression level. Enhanced green fluorescence protein lentiviral vector was constructed to down-regulate YAP in h-PDLSCs. Real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Xu et al proved that YAP/TAZ was involved in the process of periodontal tissue remodeling during OTM in rat [ 25 ]. Furthermore, they demonstrated that knockdown of YAP induced the apoptosis and inhibited the proliferation of human periodontal ligament stem cells (h-PDLSCs) through crosstalk between Erk and Bcl-2 signaling pathway, suggesting that YAP signaling pathway participated in regulating biological behaviors of h-PDLSCs [ 26 ]. Diana Huelter-Hassler also found that the activated YAP might contribute to the enhanced proliferation of HPDLCs during orthodontic tooth movement [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al proved that YAP/TAZ was involved in the process of periodontal tissue remodeling during OTM in rat [ 25 ]. Furthermore, they demonstrated that knockdown of YAP induced the apoptosis and inhibited the proliferation of human periodontal ligament stem cells (h-PDLSCs) through crosstalk between Erk and Bcl-2 signaling pathway, suggesting that YAP signaling pathway participated in regulating biological behaviors of h-PDLSCs [ 26 ]. Diana Huelter-Hassler also found that the activated YAP might contribute to the enhanced proliferation of HPDLCs during orthodontic tooth movement [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“… 16 - 18 . However, there are few studies on the expression of the Hippo/YAP pathway in human periodontal ligament stem cells (h-PDLSCs), and its exact function needs further exploration 19 - 21 . Therefore, the goal of the present study was to gain further insight into the expression and spatial distribution of YAP in h-PDLSCs, and to investigate the role of YAP in the regulation of proliferation, apoptosis, and senescence in h-PDLSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have also indicated that Yap is precisely governed by the ERK pathway [ 40 ]. We conducted western blotting assays of p-ERK and Yap to determine their relationship.…”
Section: Resultsmentioning
confidence: 99%